Envisaging Future Energy Storage Materials for Supercapacitors: An Ensemble of Preliminary Attempts. Issue 5 (3rd February 2021) - Naskar, Pappu; Chakraborty, Priyanka; Kundu, Debojyoti; Maiti, Apurba; Biswas, Biplab; Banerjee, Anjan
Abstract: Recent developments in supercapacitor technology in terms of materials and devices are reviewed herein. Beyond the conventional materials ( i. e ., carbonaceous matters, metallic compounds and conducting polymers), various multifunctional materials are reported in literature as future supercapacitive materials. A comprehensive account on such materials is lacking due to the diversified electrochemical characteristics of these materials. In this review, we bring all such non‐conventional multifunctional energy storage materials under a same umbrella for summarizing the recent advancements in supercapacitors. The envisaged multifunctional materials include metal‐organic‐frameworks (MOFs), covalent‐organic‐frameworks (COFs), heteroatom‐doped carbonaceous materials, biomass‐derived porous carbons, black phosphorous, mixed conductors, perovskite nanoparticles, polyoxometalates (POMs), redox active electrolytes, slurry materials for flow supercapacitors, thermal self‐charging materials, thermal self‐protective materials, piezoelectric materials and electrochromic materials. Inherent pros and cons of each class of material are discussed, and materials modifications towards the successful device fabrications are highlighted herewith. While the MOF‐based supercapacitors are drawing some attentions, other non‐conventional energy storage materials are truly in the nascent stage of developments. This review culminates with summary and proposed future directions for product developments. In brief, this article provides a holistic view regarding all non‐conventional multifunctional energy storage materials for future supercapacitor technology. Abstract : This review illustrates the recent advancements in materials science towards future supercapacitor technology. Apart from the conventional supercapacitive materials, various envisaged multifunctional materials are discussed herein. The inherent limitations of these non‐conventional materials are analyzed, and the mitigation strategies are highlighted. Successful realizations of device developments are also presented. However, this review accumulates all the prospective materials for advanced supercapacitors under a same umbrella.